Depression, suicide and society - Modesto Leite Rolim Neto; Vera Maria da Rocha (Universidad de Ciencias Médicas de La Habana, 2005)
Clinical observations indicate that suffering and psychic pain, by means of the repertory of languages established by depression, are associated to subjective experiences of commitment to well-being and the social recognition of this experience. The objective of this qualitative study is to understand how people interpret the meanings associated with depression and probable consequences of suicidal tendencies. 150 people, including adolescents and adults of both sexes, were investigated. Narrative interview and listening were the instruments adopted to understand the problem. Besides the patients, statements from family members and the medical team were analyzed. The target population consisted of all individuals in states of depression, with suicidal manifestations, or with a history of attempted suicide. After classifying the data, an analysis was performed to bring all types of information to the final report.   Key-words: Depression. Suicide. Society.